Decentralised Autonomous Organisations and the Corporate Form - Tse, Nathan (Victoria University of Wellington Law Review, 2020)
It has been suggested that the development of decentralised autonomous organisations (DAOs) will lead to a paradigm shift in the way we perceive businesses. DAOs ostensibly eliminate agency costs due to the absence of a board of directors, automated governance mechanisms and transparency provided by the blockchain upon which the DAO is launched. This article undertakes a comparative analysis between DAOs and corporations and questions whether DAOs really do improve the corporate form. Using a corporate governance and legal realist lens, this article suggests that a number of the purported benefits of DAOs are overly simplified. Moreover, there are several practical and legal obstacles that technological advancements and improved engineering must overcome before DAOs become a viable, mainstream organisational structure. Balancing the inevitable improvement in technology against these significant obstacles, this article predicts an incremental integration of DAOs into society through a hybrid approach, involving interim legal solutions and varying degrees of automation and decentralisation.